2022
DOI: 10.3390/hematolrep14010005
|View full text |Cite
|
Sign up to set email alerts
|

Blood Group Type Association with Head and Neck Cancer

Abstract: Background: We conducted an analysis to check whether the ABO blood group impacts the susceptibility or protection against different types of head and neck cancers. Method: We analyzed the medical records of 61,899 cancer patients from “Prof. Dr. Alexandru Trestioreanu” Institute of Oncology from Bucharest, along with the corresponding blood group type. Data were scraped using Python. For analysis, we used Chi-square test. Results: The blood group count was A (245, 45.12%) followed by 0 (160, 24.66%), B (110, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Further studies from our country have talked about other markers in oropharyngeal cancer, such as TNF- α [ 41 ], blood group type association [ 42 ], MicroRNA-486-5p and MicroRNA-10b-5p [ 43 ], as well as the use of micro-Raman and FT-IR spectra of saliva [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies from our country have talked about other markers in oropharyngeal cancer, such as TNF- α [ 41 ], blood group type association [ 42 ], MicroRNA-486-5p and MicroRNA-10b-5p [ 43 ], as well as the use of micro-Raman and FT-IR spectra of saliva [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future investigations should leverage the existing publicly available datasets and classifiers to develop, train, and externally validate new features [59]. These endeavors should also take into account clinical variables such as tumor grading and staging in developing predictive models and investigate the possible associations between characteristics such as blood types (recognized as risk factors for hypopharyngeal and oral cavity cancers) and clinical course of HNSCCs [60,61]. Future studies should also focus on increasing the interpretability of models by introducing feature maps and SHAP summary plots [62].…”
Section: Discussionmentioning
confidence: 99%
“…Further, in addition to the study of anemia in cancers, research on a link between ABO antigens and malignancies has increased in recent decades. It has recently been found that the presence of ABO antigens on the surface of cancer cells, despite their differences from those of normal cells, is nevertheless linked to the ability of these cells to evade an immune response and undergo apoptosis [32,33]. For example, Blood antigen A is linked to a higher risk of cancer of the oral cavity, whereas blood group B is linked to an increased incidence of hypopharyngeal cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been found that the presence of ABO antigens on the surface of cancer cells, despite their differences from those of normal cells, is nevertheless linked to the ability of these cells to evade an immune response and undergo apoptosis [32,33]. For example, Blood antigen A is linked to a higher risk of cancer of the oral cavity, whereas blood group B is linked to an increased incidence of hypopharyngeal cancer [32]. In the case of endometrial cancer, the positive connection of blood type A with cancer risk was seen regardless of menopausal state, body mass index, oral contraceptive usage, or family history of cancer [34].…”
Section: Discussionmentioning
confidence: 99%